An assessment of the psychometric properties of the Stoplight Pain Scale in a Canadian paediatric emergency department. Issue 7 (26th May 2021) - Ali, Samina; Morrison, Ellen; Shwetz, Seyara; Yaskina, Maryna; Rajagopal, Manasi; Estey, Andrea; Drendel, Amy L
Abstract: Objective: This study aimed to validate a novel, three faced, colour-coded, action-oriented tool: The Stoplight Pain Scale (SPS). Methods: A prospective observational cohort study was conducted at a Canadian paediatric emergency department from November 2014 to February 2017. Patients aged 3 to 12 years and their caregivers were asked to rate pain using the SPS and the Faces Pain Scale-Revised (FPS-R). Pain was measured just before analgesia administration, 30 minutes after analgesia administration, and immediately following a painful procedure. Results: A total of 227 patients were included; 26.9% (61/227) were 3 to 5 years old while 73.1% (166/227) were 6 to 12 years old. Using Cohen's κ, agreement for SPS and FPS-R was 'fair' for children (0.28 [95% confidence interval CI 0.20 to 0.36]) and 'poor' for caregivers (0.14 [95% CI 0.07 to 0.21]), at initial measurement. The SPS had 'fair' agreement between child and caregiver scores, (0.37 [95% CI 0.27 to 0.47]), compared to FPS-R which showed 'poor' agreement (0.20 [95% CI 0.12 to 0.29]). Absolute agreement between child and caregiver SPS scores improved with repeat exposure; 30 minutes after analgesia administration, caregivers and children had fair agreement (κ=0.38, 95% CI 0.28 to 0.48); they had moderate agreement directly following painful procedures (κ=0.46, 95% CI 0.34 to 0.59). Overall, 72.4% (139/192) of children and 60.2% (118/196) of caregivers preferred SPS over FPS-R. Conclusion: The SPS demonstrates fair agreement with FPS-R for children and fair-moderate agreement between children and caregivers; agreement improved with repeat use. The SPS is simple and easy to use; it may have a role in empowering direct child and family involvement in pain management. Graphical Abstract: